O acompanhamento terapêutico como prática do analista do comportamento: uma caracterização histórica com base no behaviorismo radical - Cassas, Fernando Albregard (2013)
The work presented here is motivated by a clinical intervention that began to be practiced by behavior analysts in Brazil in the early 1990s. This form prioritizes the work in the natural environment and, therefore, more likely to act directly on controlling contingencies of client behavior. This type of control seems to have established in the literature, a polarization between Therapeutic Accompaniment (TA) and the clinical based on the greater or lesser ability to control to be undertaken on the client behavior. The research presented here aims to resume and analyze the therapeutic practices of radical behaviorist base in order to establish a comparison between them and the TA, thus define whether it is possible to assert the existence of this polarization. Four sets of papers were analyzed: bases of behavior therapy: publications Skinner and Ferster about therapy, the Behavior Modification; literature on the following therapeutic approaches: Functional Analytic Therapy, Acceptance and Commitment Therapy, Behavioral Activation, the literature on the brasilian therapeutic proposals: Analytical Behavioral Therapy, Therapy of Contingencies of Reinforcement, Pragmatic Behavioral Psychotherapy and Molar and Self Therapy, beyond literature about the TA. To compose this analysis, four analytical categories were developed: core concepts for the diagnosis, intervention strategies, effectiveness and generality. The analysis of the studies cited showed that the polarization in the terms formulated above, is not true because all proposed schedule forms to ensure the generalizability of the results. Could be defined, however, the existence of a "minimum repertoire client". This concerns the modeling repertoire of verbal behavior that will allow the client to modify alone, the environment itself. And that is the reason for this study in a natural environment where the client does not have the repertoire to modify their own environment independently, the therapist operates the changing client environment in order to build a better learning condition for that client. From this, suggestions for future research are made at the end of the work